Influence of humeral head material on wear performance in anatomic shoulder joint arthroplasty - Müller, Ulrike; Braun, Steffen; Schröder, Stefan; Schröder, Mark; Sonntag, Robert; Jäger, Sebastian; Kretzer, Jan Philippe (Journal of shoulder and elbow surgery, 2017)
Background: The number of total shoulder arthroplasties has increased in the past years, with encouraging results. However, the survival of anatomic total shoulder arthroplasty (aTSA) is lower compared with that of knee and hip replacements. Wear-associated problems like loosening are well-known causes of long-term failure of aTSA. The main purpose of this study was to investigate the wear behavior of ceramic-polyethylene bearings compared with the standard metal-polyethylene bearings. Because there is a lack of valid experimental wear testing methods, the secondary aim was to develop a validated wear simulation. Methods: The wear assessment was performed using a force-controlled joint simulator for 3 × 106 cycles, and polyethylene wear was assessed gravimetrically and by particle analysis. Kinetic and kinematic data were adopted from in vivo loading measurements and from several clinical studies on shoulder joint kinematics. The reaction of the rotator cuff was simulated on the basis of a virtual soft tissue model. As activity, an abduction-adduction motion of 0°-90° lifting a load of 2 kg superimposed by an anteversion-retroversion has been chosen. Results: The studied aTSA resulted in a polyethylene wear rate of 62.75 ± 1.60 mg/106 cycles in combination with metallic heads. The ceramic heads significantly reduced the wear rate by 26.7% to 45.99 ± 1.31 mg/106. There were no relevant differences in terms of the particle characteristics. Conclusion: This is the first study that experimentally studied the wear behavior of aTSA based on patient-related and biomechanical data under load-controlled conditions. Regarding polyethylene wear, the analyzed aTSA could benefit from ceramic humeral heads.